The Bureaucratic Socialization of Library Practicum Students: A case study - J. O. Aina; N.P. Obokoh (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
This study is concerned with two things: To explore the extent to which certain aspects of the practicum students orientation may be changed in the process of actual working experience and secondly to explore the possible influence of the students working experience in future profession. An questionnaire was used on a sample of fifty library diploma students. The result showed that important changes did occur for the practicum students become substantially more bureaucratic in orientation as a result of their working experience.